Social media in sports: Brand communication strategy implementation by Jakarta Pertamina Energi - Najwandari, Naura; Wahyudin, Uud; Risanti, Yuliani Dewi; Randa, Agrian Ratu (Universitas Padjadjaran, 2025)
Background: Social media has made a significant impact on the world of sports. Today, sports clubs must compete on multiple levels, with one of the most prominent areas of competition being through social media. Despite this, volleyball in Indonesia lacks strong social media representation, highlighting the need for effective brand communication to boost its visibility. Recognizing this, PT Pertamina (Persero) established the Jakarta Pertamina Energi volleyball club, using Instagram (@jpevolley) as a key platform for its brand communication strategy. Purpose: This research aimed to explore how Jakarta Pertamina Energi implements its brand communication strategy via Instagram. Methods: It used a descriptive case study with a qualitative approach. Data were collected through interviews, literature, and documentation. Results: The study found that Jakarta Pertamina Energi follows a structured brand book that outlines key elements, such as brand objectives, target audience, brand message, personality, visual identity, and social media management. As of mid-2024, the @jpevolley account had gained over 242,000 followers, making it one of the most followed volleyball clubs in Indonesia. The account also leads in post frequency and content engagement within the sector. Conclusion: The use of a brand book ensures consistency in communication by aligning with the club’s branding objectives and strengthening overall brand presence for both the team and Pertamina products. Implications: This study suggested that brand communication in the sports industry could build brand awareness and engagement. It can also serve as a guide for other sports clubs, particularly volleyball clubs in Indonesia, to improve their social media strategies.